The benefits of HR analytics - Karmańska, Anna (Korzyści z analityki HR, 2020)
The aim of this paper is to present the benefits of using HR analytics in enterprises. The research sample included 44 practitioners employed in HR departments of Silesian enterprises. In the study a questionnaire was used where 88.6% of people surveyed indicated the benefits of using HR in the area of recruitment, and 83.6% of respondents believe that analytics affects efficiency through the better planning and utilizing of the workforce, and also positively impacts the company’s organizational culture. Employees from large companies demonstrate knowledge of HR analytics to a greater extent than those employed in the SME sector
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 30-39